Faber Polynomial for Holomorphic Functions Involving Differential Operator - Huda Fawzi Hussian; Abdul Rahman Salman Juma (Al-Qadisiyah Journal of Pure Science, 2021)
The purpose of this  paper, is to  present  differential  operator for the univalent    functions  employ a Faber Polynomial . In addition, we will introduce some inclusion properties of the operator that were obtained employ the principle of subordination between holomorphic functions.